UPAYA PENANGANAN STUNTING DI INDONESIA: ANALISIS BIBLIOMETRIK DAN ANALISIS KONTEN - Hardiyanto Rahman; Mutia Rahmah; Nur Saribulan (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2023)
The problem of stunting in Indonesia has become a national concern. The target of stunting reduction in 2024 is 14%, while in 2022 the number still at 24%. Various efforts to tackle stunting have been carried out by the Indonesia Government both at the central and regional levels, but have not been able to significantly reduce stunting. This study aims to determine the dynamics of trends in the number of studies, trends in writing from scientific disciplines, co-occurrence of author keywords, stunting handling efforts, and publication trends by region with scopus as the database. Bibliometric analysis and content analysis are used as the method in disclosing the secrecy and tendency of scientific discourse with Vosviewer application to visualise the result. This study shows that there are 103 articles published in journals related to efforts to deal with stunting in Indonesia with the year of 2021 as the year with the most publication by 33 articles. In addition, the trend of writing from the dominant disciplines related to health (medicine and nursing) is 85 articles. The highest author keywords occurrence is "stunting”, while the popular keywords were Indonesia, children, malnutrition and sanitation. In addition, there are 12 categories of stunting handling related to specific and sensitive interventions, with the most being carried out in the Indonesian region in general with 33 articles and Java Island with 62 scientific articles.